Synthesis, Structures, and Photophysical Properties of Novel Four-Coordinate Cu(I) Complexes Supported by Chelating N-Heterocyclic Carbene Ligands - Wang, Zhiqiang; Sun, Xiaojuan; Xu, Chen; Ji, Baoming (Frontiers in Chemistry, 2019)
Luminescent Cu(I) complexes are promising emitting materials for electroluminescent devices due to low cost and abundant resources as well as high emission efficiency,. whileIt is well known that N-heterocyclic carbenes (NHCs) are excellent ligands for transition metal complexes. To investigate the photophysical properties of Cu(I)-NHC complexes, a series of new mononuclear four-coordinate Cu(I) complexes supported by the diphosphine ligand bis[2-(diphenylphosphino)phenyl]ether (POP) and the NHC ligands consisted of imidazolylidene and pyrimidine units were synthesized and fully characterized. To tune the photophysical properties of these Cu(I)-NHC complexes, the NHC ligands were attached with electron-withdrawing/donating groups (fluorine, chlorine, methyl and methoxyl) at the pyrimidine unit. All of these Cu(I)-NHC complexes adopt the typical distorted tetrahedral configuration, . and tThe electron-donating groups can lead to shorter Cu−N bond distances and longer Cu−C bond distances compared to the electron-withdrawing groups. Theoretical calculation results show that the highest occupied molecular orbitals are mainly distributed on the Cu(I) ion, POP and carbene unit, while the lowest unoccupied molecular orbitals are mostly located on the pyrimidine unit of NHC ligands. The lowest energy electronic transitions of these Cu(I)-NHC complexes are mainly the metal-to-ligand charge transfer transition and ligand-to-ligand charge transfer transition. These Cu(I)-NHC complexes in solid state show tunable emissions from 530 nm to 618 nm with efficiencies of 0.5–38.1% at room temperature. The photophysical behaviors of these complexes in solid state at 298 K and 50 K match well with the thermally activated delayed fluorescence characters.